The origins of modern science from antiquity to the scientific revolution - Gal, Ofer. (Cambridge, UK ; New York, NY)
xxi, 391 sayfa
Keywords: “This book attempts to introduce to its readers major chapters in the history of science. It tries to present science as a human endeavor - a great achievement, and all the more human for it. In place of the story of progress and its obstacles or a parade of truths revealed, this book stresses the contingent and historical nature of scientific knowledge. Knowledge, science included, is always developed by real people, within communities, answering immediate needs and challenges shaped by place, culture, and historical events with resources drawn from their present and past. Chronologically, this book spans from Pythagorean mathematics to Newton's Principle. The book starts in the high Middle Ages and proceeds to introduce the readers to the historian's way of inquiry. At the center of this introduction is the Gothic Cathedral - a grand achievement of human knowledge, rooted in a complex cultural context, and a powerful metaphor for science. The book alternates thematic chapters with chapters concentrating on an era. Yet it attempts to integrate discussion of all different aspects of the making of knowledge: social and cultural settings, challenges and opportunities; intellectual motivations and worries; epistemological assumptions and technical ideas; instruments and procedures. The cathedral metaphor is evoked intermittently throughout, to tie the many themes discussed to the main lesson: that the complex set of beliefs, practices, and institutions we call science is a particular, contingent human phenomenon“ --